2020 ASEE Virtual Annual Conference Content Access Proceedings
DOI: 10.18260/1-2--34899
|View full text |Cite
|
Sign up to set email alerts
|

Learning Communities: Impact on Retention of First-year Students

Abstract: In this evidence-based practice paper, we explore the first three years of an Engineering Learning Community (ELC). The research group at our University recognizes the need to increase retention rates at the Engineering College and has created the ELC to support increased retention. Three cohorts of ELC students have been observed to determine the potential success of this project. The results from this study indicate that participation in the ELC is beneficial for first-year college students in engineering. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The quantitative research analyzed for this paper largely aligned with previous research conducted by the urban research university which demonstrated that students who participated in mentorship program as part of the broader ELC program had both an observable and statistically significantly higher GPAs than non-participating engineering students [26]. It extended the…”
Section: Discussionsupporting
confidence: 59%
“…The quantitative research analyzed for this paper largely aligned with previous research conducted by the urban research university which demonstrated that students who participated in mentorship program as part of the broader ELC program had both an observable and statistically significantly higher GPAs than non-participating engineering students [26]. It extended the…”
Section: Discussionsupporting
confidence: 59%
“…Specific to engineering, the use of hands-on collaborative design projects in the first year is also believed to be an effective method to increase student engagement, success, and retention [8]. Grounded in this research, faculty members at a large public urban research university developed an optional program for incoming first-year engineering students called the Engineering Learning Community (ELC), which has been reported on elsewhere [9], [10]. The ELC was first implemented in Fall 2016 and has been iterated each academic year since based on student feedback, best practices, and eventually an S-STEM scholarship from NSF [11].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, introductory courses are shifting from a classic lecture-lab format, to a more innovative project-based learning (PBL) format. PBL allows students to increase career path awareness, certainty in engineering, their discipline within engineering, and helps create healthy study groups and foster relationships [18,19]. In one example, a traditional lecture-lab engineering course was changed to a 2-semester innovative course with PBL on an individual and team level, which yielded increased level of engagement, better results in the desired learning outcomes and improved and more positive feedback from students [20].…”
Section: Introductionmentioning
confidence: 99%